![](https://rs.olm.vn/images/avt/0.png?1311)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(2.\left(x-5\right)-3.\left(x+7\right)=14\)
\(2x-10-3x-21=14\)
\(-x-31=14\)
\(x=-31-14\)
\(x=-45\)
\(-7.\left(5-x\right)-2.\left(x-10\right)=1\)
\(-35+7x-2x+20=1\)
\(5x-15=1\)
\(5x=1+15\)
\(5x=16\)
\(x=\frac{16}{5}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
a. 3/7 - 1/2x = 5/3
=> 1/2x = 3/7 - 5/3
=> 1/2x = 9/21 - 15/21
=> 1/2x = -26/21
=> x = -26/21 : 1/2
=> x = -26/21.2
=> x = -52/21
b. -2x + 3/14 = 1/7 - 4/21
=> -2x = -3/14 + 1/7 - 4/21
=> -2x = -18/84 + 12/84 - 16/84
=> -2x = -22/84
=> x = -22/84 : -2
=> x = -22/84 . (-1/2)
=> x = 11/84
a. 3/7 - 1/2x = 5/3
=> 1/2x = 3/7 - 5/3
=> 1/2x = 9/21 - 15/21
=> 1/2x = -26/21
=> x = -26/21 : 1/2
=> x = -26/21.2
=> x = -52/21
b. -2x + 3/14 = 1/7 - 4/21
=> -2x = -3/14 + 1/7 - 4/21
=> -2x = -18/84 + 12/84 - 16/84
=> -2x = -22/84
=> x = -22/84 : -2
=> x = -22/84 . (-1/2)
=> x = 11/84
![](https://rs.olm.vn/images/avt/0.png?1311)
\(a,-7x+7=21\)
\(\Rightarrow-7x=21-7=14\)
\(\Rightarrow x=-2\)
\(b,9x+11=20x+66\)
\(\Rightarrow9x-20x=66-11=55\)
\(\Rightarrow-11x=55\)
\(\Rightarrow x=-5\)
\(c,3^3.x+4^2=5^2.x-2.\left(2017\right)^0\)
\(27x+16=25x-2\)
\(\Rightarrow16+2=25x-27x=-2x\)
\(\Rightarrow-2x=18\)
\(\Rightarrow x=-9\)
![](https://rs.olm.vn/images/avt/0.png?1311)
a)3x - 105 : 21 = 19
3x - 5 = 19
3x = 19 + 5
3x = 24
x = 24 : 8
x = 3
b, x - 7 = 14 - 3 . 23
x - 7 = 14 - 3 . 8
x - 7 = 14 - 24
x - 7 = -10
x = (-10) + 7
x = -3
HT và $$$
Bài 2:
a) 3x - 105 : 21= 19 b) x - 7= 14 - 3 . 2^3
3x - 5 = 19 x - 7= 14 - 3.8
3x = 19+ 5 x - 7= 14 - 24
3x = 24 x - 7= -10
x = 24 : 3 x = -10+7
x = 8 x = -3
![](https://rs.olm.vn/images/avt/0.png?1311)
\(x\cdot\frac{5}{7}+\frac{1}{14}=\frac{2}{21}\)
\(x\cdot\frac{5}{7}=\frac{2}{21}-\frac{1}{14}\)
\(x\cdot\frac{5}{7}=\frac{1}{42}\)
\(x=\frac{1}{42}:\frac{5}{7}\)
\(x=\frac{1}{30}\)
x.5/7 + 1/14 = 2/21
=> x .5/7 = 2/21 - 1/14
x .5/7 = 1/42
=> x = 1/42 : 5/7
x = 1/30
![](https://rs.olm.vn/images/avt/0.png?1311)
d) |2x – 5| –7 = 22
| 2x -5 | = 22+7
| 2x -5 | = 29
TH1: 2x-5 = -29
2x = -29+5
2x= -24
x= -24:2
x= -12
TH2: 2x -5 =29
2x = 29+5
2x= 34
x= 34:2
x= 17
Vậy...
![](https://rs.olm.vn/images/avt/0.png?1311)
Bài 1:
a) \(\frac{16}{15}.\frac{\left(-5\right)}{14}.\frac{54}{24}.\frac{56}{21}\)
\(=\frac{4.2.2}{5.3}.\frac{\left(-5\right)}{2.7}.\frac{3.3}{4}.\frac{8}{3}\)
\(=\frac{4.2.2.\left(-5\right).3.3.8}{5.3.2.7.4.3}\)
\(=\frac{-16}{7}\)
b) \(\frac{7}{3}.\frac{\left(-5\right)}{2}.\frac{15}{21}.\frac{4}{\left(-5\right)}\)
\(=\frac{7}{3}.\frac{\left(-5\right)}{2}.\frac{5}{7}.\frac{2.2}{\left(-5\right)}\)
\(=\frac{7.\left(-5\right).5.2.2}{3.2.7.\left(-5\right)}\)
\(=\frac{10}{3}\)
Bài 2:
a) \(\frac{21}{24}.\frac{11}{9}.\frac{5}{7}=\frac{7}{8}.\frac{11}{9}.\frac{5}{7}=\frac{11.5}{8.9}=\frac{55}{72}\)
b) \(\frac{5}{23}.\frac{17}{26}+\frac{5}{23}.\frac{9}{26}\)
\(=\frac{5}{23}.\left(\frac{17}{26}+\frac{9}{26}\right)=\frac{5}{23}.1=\frac{5}{23}\)
c) \(\left(\frac{3}{29}-\frac{1}{5}\right).\frac{29}{3}=\frac{3}{29}.\frac{29}{3}-\frac{1}{5}.\frac{29}{3}\)
\(=1-1\frac{14}{15}=\frac{14}{15}\)
Bài 3:
a) x/5 = 2/5
=> x =2
b) -4/x = 20/14 = 10/7
=> -4/x = 10/7
=> x.10 = (-4).7
x.10 = - 28
x= -28 :10
x= -2,8
c) 4/7 = 12/x = 12/ 21
=> 12/x = 12/21
=> x = 21
d) 3/7 = x / 21 = 9/21
=> x/21 = 9/21
=> x= 9
![](https://rs.olm.vn/images/avt/0.png?1311)
a; \(\dfrac{93}{17}\): \(x\) + (- \(\dfrac{21}{17}\)) : \(x\) + \(\dfrac{22}{7}\): \(\dfrac{22}{3}\) = \(\dfrac{5}{14}\)
\(\dfrac{94}{17}\) \(\times\) \(\dfrac{1}{x}\) - \(\dfrac{21}{17}\) \(\times\) \(\dfrac{1}{x}\) + \(\dfrac{3}{7}\) = \(\dfrac{5}{14}\)
\(\dfrac{72}{17}\) \(\times\) \(\dfrac{1}{x}\) + \(\dfrac{3}{7}\) = \(\dfrac{5}{14}\)
\(\dfrac{72}{17x}\) = \(\dfrac{5}{14}\) - \(\dfrac{3}{7}\)
\(\dfrac{72}{17x}\) = - \(\dfrac{1}{14}\)
17\(x\) = 72.(-14)
17\(x\) = - 1008
\(x\) = - 1008 : 17
\(x\) = - \(\dfrac{1008}{17}\)
Vậy \(x\) \(=-\dfrac{1008}{17}\)
b; - \(\dfrac{32}{27}\) - (3\(x\) - \(\dfrac{7}{9}\))3 = - \(\dfrac{24}{27}\)
- \(\dfrac{32}{27}\) + \(\dfrac{24}{27}\) = (3\(x\) - \(\dfrac{7}{9}\))3
(3\(x-\dfrac{7}{9}\))3 = - \(\dfrac{8}{27}\)
(3\(x-\dfrac{7}{9}\))3 = (- \(\dfrac{2}{3}\))3
3\(x-\dfrac{7}{9}\) = - \(\dfrac{2}{3}\)
3\(x\) = - \(\dfrac{2}{3}\) + \(\dfrac{7}{9}\)
3\(x\) = \(\dfrac{1}{9}\)
\(x\) = \(\dfrac{1}{9}\) : 3
\(x\) = \(\dfrac{1}{27}\)
Vậy \(x=\dfrac{1}{27}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
1/3(2x-5)=-2/3-3/2=-13/6
2x-5=-13/6:1/3=-13/2
2x=-13/2+5
2x=-3/2
x=-3/2:2=-3/4
Trương Ứng Hòa